The Fatimid Legacy and the Foundation of the Modern Nizari Ismaili Imamate - Beben, Daniel (I. B. Tauris., 2017)
The Fatimid era is ubiquitous today in the discourse of the Nizari Ismaili imamate. Yet this was not always the case. As with other societies and religious communities the world over, the arrangement and presentation of history in the Ismaili tradition has evolved in the course of time, with new historiographical agendas and subjects of emphasis emerging or receding in response to changes in the political and social contexts. In this chapter the place of the Fatimids in the cultural memory of the Nizari Ismailis in the post-Mongol era will be explored. 2 It will be argued that the emphasis placed on the Fatimid era in present-day Nizari discourse is a relatively recent development, rooted in the dynamic changes that occurred in the social and political context of the community in the 18th and 19th centuries.